A professional approach Microsoft Office Word : - Hinkle, Deborah (McGraw-Hill, 2005)
McGraw-Hill Technology Education’s Professional Approach Series presents exercises in real-life business situations so students get hands-on experience working on actual projects--the best way to prepare them for the on-the-job challenges they'll face. Each lesson contains up to 25 skill-applications and 5 end-of-unit skill-applications that take students from simple to complex situations. The Office 2003 texts complete instruction in all skill sets and activities for the appropriate Microsoft Office Specialist Certification (MOS) Exams.